2020
DOI: 10.1002/bab.1856
|View full text |Cite
|
Sign up to set email alerts
|

Viral IL‐10 promotes cell proliferation and cell cycle progression via JAK2/STAT3 signaling pathway in nasopharyngeal carcinoma cells

Abstract: Epstein–Barr virus (EBV) is positively related to the morbidity of nasopharyngeal carcinoma (NPC) in Asia. After infection, EBV can produce several proteins, including viral interleukin‐10 (vIL‐10). But the mechanism by which vIL‐10 contributes to NPC cell proliferation and cell cycle progression is not well understood. In this study, EBV negative and positive cell lines, and the JAK2/STAT3 signal pathway inhibitor AG490 were used to illustrate the role of vIL‐10 in NPC. Cell proliferation and cell cycle were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…[197][198][199] Studies of both solid and hematological EBV-associated malignancies demonstrated higher levels of IL-10 expression compared to EBV-negative malignancies in the same anatomical region or the same cells of origin [200][201][202][203][204], which are linked to local immune suppression or local enhanced immune cell tolerance [205]. In fact, IL-10 is known to (i) downregulate the expression of major histocompatibility complex (MHC) class I and II antigens of antigen-presenting cells (APCs) [191], (ii) induce Tregs [190], which in turn (iii) inhibit T-cell proliferation and IFN-γ secretion [192], and (iv) functionally block cytotoxicity of CD8 + T cells [188] causing an immune-suppressive TME. Furthermore, in vitro knockdown of IL-10 switches latent EBV-infected tumor cells to the lytic form leading to tumor cell death.…”
Section: Soluble Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[197][198][199] Studies of both solid and hematological EBV-associated malignancies demonstrated higher levels of IL-10 expression compared to EBV-negative malignancies in the same anatomical region or the same cells of origin [200][201][202][203][204], which are linked to local immune suppression or local enhanced immune cell tolerance [205]. In fact, IL-10 is known to (i) downregulate the expression of major histocompatibility complex (MHC) class I and II antigens of antigen-presenting cells (APCs) [191], (ii) induce Tregs [190], which in turn (iii) inhibit T-cell proliferation and IFN-γ secretion [192], and (iv) functionally block cytotoxicity of CD8 + T cells [188] causing an immune-suppressive TME. Furthermore, in vitro knockdown of IL-10 switches latent EBV-infected tumor cells to the lytic form leading to tumor cell death.…”
Section: Soluble Mediatorsmentioning
confidence: 99%
“…This also synergizes with chemotherapy and thus leads to cell death [206] suggesting that IL-10 exhibits a key role in EBV-positive malignancies. Furthermore, IL-4, IL-6 and IL-13 are frequently upregulated in EBV-positive malignancies and might have relevance in the development and/or maintenance of EBV-associated malignancies [188,207,208]. Regarding IL-1β, increased levels were found in the TILs of EBV-positive GC [185].…”
Section: Soluble Mediatorsmentioning
confidence: 99%
“…Therefore, we choose the mesangial cells treated with high glucose as an in vitro model, which was consistent with other findings. In this study, high glucose promotes the release of IL-6 which can promote cycle-related genes expression, and thus enhance the cell proliferation ( Ren et al, 2020 ). After intervention with VHH-0031, it could inhibit high-glucose-induced proliferation of mesangial cells.…”
Section: Discussionmentioning
confidence: 94%
“…Studies had indicated that high glucose could promote JAK2 and STAT3 expression ( Nahman et al, 1992 ). Cyclin D1 was one of the important target genes of STAT3 ( Ren et al, 2020 ). Cell cycle disorders is an important cause of abnormal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, EBV can produce several proteins, including viral interleukin-10 (IL-10). IL-10 in turn can trigger the production of IL-6, interfere with the cellmediated immune response and contribute to immortalization of B cells [64][65][66]. All these phenomena may play a potential role in SS immunopathogenesis including the development of SS-related lymphoma.…”
Section: B Cellsmentioning
confidence: 99%